Interprofessional education among musculoskeletal healthcare professions: A scoping review. - Ismail, Fatima; Myburgh, Corrie; Downing, Charlene; Makkink, Andrew (Journal of Chiropractic Education (Allen Press Publishing Services Inc.), 2025)
To examine peer-reviewed literature involving undergraduate interprofessional education (IPE) focusing on musculoskeletal (MSK) healthcare professions. Methodological searches were conducted on electronic databases PubMed, Scopus, ERIC, and ProQuest. No date restrictions were applied. English sources (qualitative and quantitative methodological studies, conference papers and proceedings, systematic reviews, grey literature, unpublished materials, theses, and dissertations) were included. A researcher, independent reviewer, and research librarian completed the search and data extraction from June to October 2023. Disagreements were resolved by discussion. ATLAS.ti was used to analyze data by generating codes linked to the text. Findings were reported in a narrative format and by using tables. Initially, 2894 articles were retrieved and screened for relevance. After rigorous screening procedures, 18 articles from various countries were deemed eligible for inclusion. The included studies were conducted within the date range of 2010 to 2024. The included studies employed mixed methods (n = 9), quantitative (n = 5), and qualitative (n = 4) approaches. Combined medical and physiotherapy student cohorts were prominently featured in 67% (n = 12) of the reviewed studies. All 18 studies incorporated the implementation and/or evaluation of an IPE intervention. Thematic analysis revealed 5 overarching themes, encompassing the benefits, barriers, interventions, strategies, evaluation, and general findings related to IPE. The reviewed literature emphasizes a significant gap in IPE initiatives concerning various MSK health providers, including chiropractors, podiatrists, biokineticists, and osteopaths. This paucity accentuates the need for further exploration and evaluation of IPE within MSK-specific contexts, crucial for addressing and mitigating the escalating global burden of MSK diseases.